Novel characterization of lead-based micro-alloys for battery applications. (1st December 2021) - Wall, Michael T.; Carl, Matthew; Smith, Jesse; Ren, Yang; Raiford, Matthew; Hesterberg, Travis; Ellis, Tim; Young, Marcus L.
Highlights: Synchrotron Radiation XRD is used as a novel characterization technique for battery materials. Micro-alloying Bi with Pb provides grain coarsening. Micro-alloying Ba with Pb prevents grains from growing. Synchrotron provides structural details of micro-alloy Pb material during thermal cycling. Abstract: Although Pb-alloy acid batteries have been incorporated in vehicles for decades, a significant gap exists in the scientific understanding of minor alloying elements in the complex Pb-alloy grid materials. The aim of this research is to close this gap by using modern analytical techniques to examine the effects associated with adding minor alloying elements, less than 100 ppm, in Pb-alloy grid materials during isothermal holds and thermal cycling at relatively high temperatures. In this study, pure Pb, Pb-Bi, and Pb-Ba foils are examined using high-energy synchrotron radiation X-ray diffraction measurements during in situ isothermal holding at 85 °C and thermal cycling from RT to 85°C to analyze the grain inhibition and phase evolution. It is observed that Ba inhibits grain growth while Bi does not, when compared to pure Pb. Furthermore, no obvious phase evolution in any of the three cases is observed. After the synchrotron radiation X-ray diffraction measurements, the three materials are examined ex situ using scanning electron microscopy to verify the results. Additionally, baseline sulfation studies were performed in a solution of approximately 5 M H2 SO4 and Pb-Bi and Pb-Ba were added to the electrochemical cell to undergo cyclic voltammetry.